The Program That Involves Some Integrated Lesson Topics to Help Students Understand How to Create Simple Sentences - FIRMANSYAH DIYATA (Universitas Widyatama, 2019)
Some teachers believe that serving their students by a suitable approach is the most important. It may be true if they have already had students with sufficient English knowledge. If they don